Mapping selfies and memes as Touch - Andreallo, Fiona (Springer Nature, 2022)
This open access book offers a rich and nuanced analysis of digitally networked socialities as culturally meaningful relationships of Touch. Focusing on the ways Touch is practised in everyday social interactions serves as a basis for how Touch is understood as multiply significant - physically, emotionally, intellectually and politically. Andreallo initiates a map of the fundamentals of Touch and how they can be considered for future research in considering digitally networked cultures. This map also serves as a basis for closely examining selfies and memes. Examining social networks of Touch, Andreallo focuses on a specific example of the PrettyGirlsUglyFaces meme and ugly selfies(uglies). Through this example, memes and selfies are mapped as Touch involving textures of both intimacy and violence. Andreallo also discusses technological seamlessness and cultural semefulness as conversations of social relationships of Touch, and proposes the term semeful sociabilities to describe how the everyday technological self engages in practices of Touch. This book is a compact, approachable insight into selfies and memes as everyday culturally networked Touch relationships that also offers a way forward in recognising technological relationships as culturally meaningful.